(untitled) (Research, Society and Development, 2022)
Objective: This systematic review protocol will examine studies on the effect of acupuncture and herbal medicine on weightloss in obese adults. Methods: Searches will be carried out in MEDLINE (via PubMed), EMBASE (via ScienceDirect), LILACS (via VHL) and Cochrane databases until April 2022. Observational (cohort, case-control and cross-sectional) and experimental studies will be included ( clinical trials), two independent investigators will use Rayyan QCRI software for article retrieval, and Mendeley Reference Manager software will be used for reference management. After reading them in full, the articles will be selected according to the eligibility criteria. Results: The synthesis of evidence data will be approached from the relationship between the effect of using acupuncture and phytotherapy on weight loss. Conclusion: Given the above, the importance of this review protocol is highlighted to elucidate the current evidence on the use of integrative practices: acupuncture and herbal medicine for weight loss in obese adults.